Neoliberalism in Ecuador after Correa: A surprise turn or according to economic elites' plan? - Thomas Chiasson-LeBel (European Review of Latin American and Caribbean Studies, 2019)
This article examines economic elites’ reactions to early efforts by Ecuador’s left government to limit their clout. Elites developed an infrastructure of dissent to promote their interests. Some chambers of commerce and industry adapted their strategies to promote ideas and public figures that would gain increasing public and political prominence. Domestic conglomerates used different strategies to regain influence: ostentatious attempts to use economic power to capture the highest sphere of government offered promising results when accompanied by electoral wins, but active yet subtler strategies to improve their public image allowed some conglomerates to dispute the definition of development with the state and to cast themselves as representing collective well-being. By showing how economic elites used the global economic conjuncture and the trend of corporate social responsibility to advance their economic program, this article demonstrates that studying the agency of economic elites is essential for understanding how business interests shape political outcomes. Resumen: Neoliberalismo en Ecuador tras Correa: ¿Giro inesperado o de acuerdo al plan de la elite económica? Este artículo examina las reacciones de las élites económicas ante los primeros esfuerzos del gobierno de izquierda de Ecuador para limitar su influencia. Las élites desarrollaron una infraestructura de disidencia para promover sus intereses. Algunas cámaras de comercio e industria adaptaron sus estrategias para promover ideas y figuras públicas que ganarían cada vez más protagonismo público y político. Los conglomerados nacionales utilizaron diferentes estrategias para recuperar su influencia: los ostentosos intentos de utilizar el poder económico para ocupar la esfera más alta del gobierno ofrecieron resultados prometedores cuando iban acompañados de victorias electorales, pero las estrategias activas y más sutiles para mejorar su imagen pública permitieron a algunos conglomerados cuestionar la definición de desarrollo con el estado y así presentarse como representantes del bienestar colectivo. Al mostrar cómo las élites económicas usaron la coyuntura económica global y la tendencia de la responsabilidad social corporativa para avanzar en su programa económico, este artículo demuestra que estudiar la agencia de las élites económicas es esencial para comprender cómo los intereses comerciales dan forma a los resultados políticos.